Assessment of a Social Media‐Based Method for Determining Raptor Diet - Leo Biggs; Greg S. Baxter; Stephen J. S. Debus; Neal Finch; Anysha Riggs; Hayden Houweling; Melissa Appleby; Peter J. Murray (Ecology and Evolution)
ABSTRACT Accurate dietary information is important to improve ecological knowledge and assist in the conservation of threatened predators and their prey. Globally, many raptor populations are threatened and would benefit from accurate diet information. However, the existing methods of collecting diets can be time consuming, biased, or unfeasible for large spatial areas. Use of citizen science has been suggested to address these issues, but critical analysis of the method and comparison with existing methods is largely incomplete. Here, we evaluate the accuracy, efficiency, and biases of raptor diets data mined from social media. Two Australian coastal raptor species, Eastern Osprey (Pandion haliaetus cristatus) and White‐bellied Sea‐Eagles (WBSE) (Haliaeetus leucogaster), were searched on Facebook and Instagram. Photographs and videos showing these raptors in possession of prey items were catalogued to form diets. The time taken to collect and identify prey items was recorded. The social media method was effective, producing large quantities of high quality media that recorded raptors and their prey. Study analyses utilised 1484 Eastern Osprey and 501 WBSE prey items posted between 2019 and 2023. Diet completeness was high, with a greater number of prey species observed in each region than previous studies. The prey identification rate to the family level was comparable with other direct visual observation methods at 58%. A consistent diet was observed between social media platforms. Eastern Osprey diet was similar to previous studies in New South Wales, except for a single prey family. WBSE diet was more varied than previous studies, which appeared biased by a locally high availability of certain prey species. The social media method was also efficient, with prey items collected and identified at a rate of 0.21 h per prey item; over 25 times faster than other raptor diets collected using direct visual observations. Furthermore, the social media method countered the biases of alternative methods such as small population samples, restricted spatial coverage, and over or under‐representation of animal classes. However, it produced new biases requiring quantification such as human activity hotspots, potential difficulty identifying small prey, and an over‐representation of easily identifiable or ‘interesting’ prey. Overall, the use of social media was effective and efficient at recording raptor diet and is encouraged for other raptors and predators.